Seismic-scale fault characterization for geologic carbon storage using legacy data and machine learning - Lianjie Huang; David Li; Kai Gao; Adewale Amosu; George El-Kaseeh; Tom Bratton; Yingcai Zheng; Kevin McCormack; Rajesh Pawar; Bailian Chen; William Ampomah (International Journal of Greenhouse Gas Control, 2026)

A search for hydroacoustic signals from bolides - Peter Brown; Luke McFadden; David McCormack; Mareike Adams; Denis Vida (Icarus, 2026)

A comparative analysis of states of stress for analyzing fault slip potential - Kevin L. McCormack; Tom Bratton; Adewale Amosu; Lianjie Huang; David Li; Jeffrey Burghardt; William Ampomah (International Journal of Greenhouse Gas Control, 2025)

Animal population decline and recovery after severe fire: Relating ecological and life history traits with expert estimates of population impacts from the Australian 2019-20 megafires - Michelle Ensbey; Sarah Legge; Chris J. Jolly; Stephen T. Garnett; Rachael V. Gallagher; Mark Lintermans; Dale G. Nimmo; Libby Rumpff; Ben C. Scheele; Nick S. Whiterod; John C.Z. Woinarski; Shane T. Ahyong; et al. (Biological Conservation, 2023)

The conservation impacts of ecological disturbance: Time‐bound estimates of population loss and recovery for fauna affected by the 2019–2020 Australian megafires - Sarah Legge; Libby Rumpff; John C. Z. Woinarski; Nick S. Whiterod; Michelle Ward; Darren G. Southwell; Ben C. Scheele; Dale G. Nimmo; Mark Lintermans; Hayley M. Geyle; Stephen T. Garnett; Brittany Hayward‐Brown; et al. (Global Ecology and Biogeography, 2022)
Aim After environmental disasters, species with large population losses may need urgent protection to prevent extinction and support recovery. Following the 2019–2020 Australian megafires, we estimated population losses and recovery in fire‐affected fauna, to inform conservation status assessments and management. Location Temperate and subtropical Australia. Time period 2019–2030 and beyond. Major taxa Australian terrestrial and freshwater vertebrates; one invertebrate group. Methods From > 1,050 fire‐affected taxa, we selected 173 whose distributions substantially overlapped the fire extent. We estimated the proportion of each taxon’s distribution affected by fires, using fire severity and aquatic impact mapping, and new distribution mapping. Using expert elicitation informed by evidence of responses to previous wildfires, we estimated local population responses to fires of varying severity. We combined the spatial and elicitation data to estimate overall population loss and recovery trajectories, and thus indicate potential eligibility for listing as threatened, or uplisting, under Australian legislation. Results We estimate that the 2019–2020 Australian megafires caused, or contributed to, population declines that make 70–82 taxa eligible for listing as threatened; and another 21–27 taxa eligible for uplisting. If so‐listed, this represents a 22–26% increase in Australian statutory lists of threatened terrestrial and freshwater vertebrates and spiny crayfish, and uplisting for 8–10% of threatened taxa. Such changes would cause an abrupt worsening of underlying trajectories in vertebrates, as measured by Red List Indices. We predict that 54–88% of 173 assessed taxa will not recover to pre‐fire population size within 10 years/three generations. Main conclusions We suggest the 2019–2020 Australian megafires have worsened the conservation prospects for many species. Of the 91 taxa recommended for listing/uplisting consideration, 84 are now under formal review through national processes. Improving predictions about taxon vulnerability with empirical data on population responses, reducing the likelihood of future catastrophic events and mitigating their impacts on biodiversity, are critical.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Soil biota, carbon cycling and crop plant biomass responses to biochar in a temperate mesocosm experiment - Sarah A. McCormack; Nick Ostle; Richard D. Bardgett; David W. Hopkins; M. Glória Pereira; Adam J. Vanbergen (Plant and Soil, 2019)

Adapting Stand‐Alone Renewable Energy Technologies for the Circular Economy through Eco‐Design and Recycling - John Gallagher; Biswajit Basu; Maria Browne; Alan Kenna; Sarah McCormack; Francesco Pilla; David Styles (Journal of Industrial Ecology, 2019)
Summary Renewable energy (RE) technologies are looked upon favorably to provide for future energy demands and reduce greenhouse gas (GHG) emissions. However, the installation of these technologies requires large quantities of finite material resources. We apply life cycle assessment to 100 years of electricity generation from three stand‐alone RE technologies—solar photovoltaics, run‐of‐river hydro, and wind—to evaluate environmental burden profiles against baseline electricity generation from fossil fuels. We then devised scenarios to incorporate circular economy (CE) improvements targeting hotspots in systems’ life cycle, specifically (1) improved recycling rates for raw materials and (ii) the application of eco‐design. Hydro presented the lowest environmental burdens per kilowatt‐hour of electricity generation compared with other RE technologies, owing to its higher efficiency and longer life spans for main components. Distinct results were observed in the environmental performance of each system based on the consideration of improved recycling rates and eco‐design. CE measures produced similar modest savings in already low GHG emissions burdens for each technology, while eco‐design specifically had the potential to provide significant savings in abiotic resource depletion. Further research to explore the full potential of CE measures for RE technologies will curtail the resource intensity of RE technologies required to mitigate climate change.

Mycorrhizal fungi and roots are complementary in foraging within nutrient patches - Lei Cheng; Weile Chen; Thomas S. Adams; Xing Wei; Le Li; Michael Luke McCormack; Jared L. DeForest; Roger T. Koide; David M. Eissenstat (Ecology, 2016)
The roots of the majority of tree species are associated with either arbuscular mycorrhizal (AM) or ectomycorrhizal (EM) fungi. The absorptive roots of tree species also vary widely in their diameter. The linkages between root thickness, mycorrhiza type and nutrient foraging are poorly understood. We conducted a large root ingrowth experiment in the field to investigate how absorptive roots of varying thickness and their associated fungi (AM vs. EM) exploit different nutrient patches (inorganic and organic) in a common garden. In nutrient‐rich patches, thin‐root tree species more effectively proliferated absorptive roots than thick‐root tree species, whereas thick‐root tree species proliferated more mycorrhizal fungal biomass than thin‐root tree species. Moreover, nutrient patches enriched with organic materials resulted in greater root and mycorrhizal fungal proliferation compared to those enriched with inorganic nutrients. Irrespective of root morphology, AM tree species had higher root foraging precision than mycorrhizal hyphae foraging precision within organic patches, whereas EM tree species exhibited the opposite. Our findings that roots and mycorrhizal fungi are complementary in foraging within nutrient patches provide new insights into species coexistence and element cycling in terrestrial ecosystems.

Early season root production in relation to leaf production among six diverse temperate tree species - M. Luke McCormack; Katie P. Gaines; Melissa Pastore; David M. Eissenstat (Plant and Soil, 2015)

Variability in root production, phenology, and turnover rate among 12 temperate tree species - M. Luke McCormack; Thomas S. Adams; Erica A. H. Smithwick; David M. Eissenstat (Ecology, 2014)
The timing of fine root production and turnover strongly influences both the seasonal potential for soil resource acquisition among competing root systems and the plant fluxes of root carbon into soil pools. However, basic patterns and variability in the rates and timing or fine root production and turnover are generally unknown among perennial plants species. We address this shortfall using a heuristic model relating root phenology to turnover together with three years of minirhizotron observations of root dynamics in 12 temperate tree species grown in a common garden. We specifically investigated how the amount and the timing of root production differ among species and how they impact estimates of fine root turnover. Across the 12 species, there was wide variation in the timing of root production with some species producing a single root flush in early summer and others producing roots either more uniformly over the growing season or in multiple pulses. Additionally, the pattern and timing of root production appeared to be consistent across years for some species but varied in others. Root turnover rate was related to total root production ( P

The Influence of Spatial Filters on Infrasound Array Responses - David J. Brown; Curt A. L. Szuberla; David McCormack; Pierrick Mialle (Pure and Applied Geophysics, 2014)

Regional scale patterns of fine root lifespan and turnover under current and future climate - M. Luke McCormack; David M. Eissenstat; Anantha M. Prasad; Erica A. H. Smithwick (Global Change Biology, 2013)
Fine root dynamics control a dominant flux of carbon from plants and into soils and mediate potential uptake and cycling of nutrients and water in terrestrial ecosystems. Understanding of these patterns is needed to accurately describe critical processes like productivity and carbon storage from ecosystem to global scales. However, limited observations of root dynamics make it difficult to define and predict patterns of root dynamics across broad spatial scales. Here, we combine species‐specific estimates of fine root dynamics with a model that predicts current distribution and future suitable habitat of temperate tree species across the eastern United States ( US ). Estimates of fine root lifespan and turnover are based on empirical observations and relationships with fine root and whole‐plant traits and apply explicitly to the fine root pool that is relatively short‐lived and most active in nutrient and water uptake. Results from the combined model identified patterns of faster root turnover rates in the North Central US and slower turnover rates in the Southeastern US . Portions of Minnesota, Ohio, and Pennsylvania were also predicted to experience >10% increases in root turnover rates given potential shifts in tree species composition under future climate scenarios while root turnover rates in other portions of the eastern US were predicted to decrease. Despite potential regional changes, the average estimates of root lifespan and turnover for the entire study area remained relatively stable between the current and future climate scenarios. Our combined model provides the first empirically based, spatially explicit, and spatially extensive estimates of fine root lifespan and turnover and is a potentially powerful tool allowing researchers to identify reasonable approximations of forest fine root turnover in areas where no direct observations are available. Future efforts should focus on reducing uncertainty in estimates of root dynamics by better understanding how climate and soil factors drive variability in root dynamics of different species.

Phytophagous insect community assembly through niche conservatism on oceanic islands - David H. Hembry; Tomoko Okamoto; Gerald McCormack; Rosemary G. Gillespie (Journal of Biogeography, 2013)
Aim To determine whether a community of phytophagous insects on oceanic islands (the fauna of insects feeding internally on G lochidion trees in south‐eastern P olynesia) was assembled predominantly through niche conservatism or adaptive radiation. Location The islands of south‐eastern P olynesia (southern C ook, A ustral, S ociety, T uamotu‐ G ambier and M arquesas archipelagos) in the C ook I slands and F rench P olynesia. Methods Internally feeding insects were collected as larvae from 23 endemic species of G lochidion ( E uphorbiaceae s.l., P hyllanthaceae: P hyllanthus s.l.) trees on 20 islands in south‐eastern P olynesia, reared and identified. Rearing records were compared with host records previously known from the literature and museum collections of closely related taxa in A sia and A ustralasia. Results Ninety per cent of insect specimens collected fall into five taxa previously known to attack G lochidion in A sia and A ustralasia (≥ 6000 km distant), indicating a strong role for niche conservatism in the assembly of this community. Three of these taxa, two seed‐feeding moths ( G racillariidae: E picephala ; T ortricidae: T ritopterna ) and a leaf‐mining moth ( G racillariidae: D iphtheroptila ) are only known from Phyllanthaceae or Euphorbiaceae s.l. on continents. Two more taxa, another leaf‐mining moth ( G racillariidae: C aloptilia ) and a leaf‐rolling moth ( T ortricidae: D udua ), contain many species known only from P hyllanthaceae on continents, and are also very likely to represent examples of niche conservatism. Conversely, many numerically dominant insect taxa known from G lochidion on continents (such as parasitoid H ymenoptera) are not reported from south‐eastern P olynesia. This indicates that the insular community represents a subset of those taxa from the continental community, consistent with the well‐established P acific diversity gradient. Main conclusions These findings indicate that niche conservatism can play an important role in the assembly of phytophagous insect communities on oceanic islands, despite the constraints that specialization might be expected to pose on successful establishment. As a result of this niche conservatism, these communities may represent less species‐rich versions of continental tropical communities rather than non‐analogue insular ecosystems.

Aspirin and NSAID use and lung cancer risk: a pooled analysis in the International Lung Cancer Consortium (ILCCO) - Valerie A. McCormack; Rayjean J. Hung; Darren R. Brenner; Heike Bickeböller; Albert Rosenberger; Joshua E. Muscat; Philip Lazarus; Anne Tjønneland; Søren Friis; David C. Christiani; Eun-mi Chun; Loic Le Marchand; et al. (Cancer Causes & Control, 2011)

The Molecular Phylogeny of a Nematode-Specific Clade of Heterotrimeric G-Protein α-Subunit Genes - Damien M. O’Halloran; David A. Fitzpatrick; Grace P. McCormack; James O. McInerney; Ann M. Burnell (Journal of Molecular Evolution, 2006)